Diverse urban plantings managed with sufficient resource availability can increase plant productivity and arthropod diversity - Muller, Jonathon N.; Loh, Susan; Braggion, Ligia; Cameron, Stephen; Firn, Jennifer L. (Frontiers in Plant Science, 2014)
Buildings structures and surfaces are explicitly being used to grow plants, and these ‘urban plantings’ are typically designed for aesthetic value. Urban plantings also have the potential to contribute significant ‘ecological values’ by increasing urban habitat for animals such as arthropods and by increasing plant productivity. In this study, we evaluated how the provision of these additional ecological values is affected by plant species richness; the availability of essential resources for plants, such as water, light, space; and soil characteristics. We sampled 33 plantings located on the exterior of three buildings in the urban centre of Brisbane, Australia (subtropical climatic region) over two, six week sampling periods characterised by different temperature and rainfall conditions. Plant cover was estimated as a surrogate for productivity as destructive sampling of biomass was not possible. We measured weekly light levels (photosynthetically active radiation), plant CO2 assimilation, soil CO2 efflux, and arthropod diversity. Differences in plant cover were best explained by a three-way interaction of plant species richness, management water regime and sampling period. As the richness of plant species increased in a planter, productivity and total arthropod richness also increased significantly - likely due to greater habitat heterogeneity and quality. Overall we found urban plantings can provide additional ecological values if essential resources are maintained within a planter such as water, light and soil temperature. Diverse urban plantings that are managed with these principles in mind can contribute to the attraction of diverse arthropod communities, and lead to increased plant productivity within a dense urban context.